Progressive loss of speech output and orofacial dyspraxia associated with frontal lobe hypometabolism. Issue 4 (April 1991) - Tyrrell, P J; Kartsounis, L D; Frackowiak, R S; Findley, L J; Rossor, M N
Abstract : Three patients are described with slowly progressive loss of speech and dysarthria associated with orofacial dyspraxia, initially with intact written language, who subsequently developed more widespread cognitive abnormalities. Positron emission tomography (PET) revealed bifrontal hypometabolism in all of the patients, most marked in the inferior and lateral portions of both frontal lobes, with some extension into the parietal and temporal cortices in one case. These patients may represent a further example of focal progressive cortical degeneration.